Assessment of myocardial deformation with CMR: a comparison with ultrasound speckle tracking in a cohort of highly trained endurance athletes - Domenech-Ximenos, B.; Sanz-De La Garza, M.; Sepulveda-Martinez, A.; Lorenzatti, D.; Simard, F.; Crispi, F.; Perea, R. J.; Prat-Gonzalez, S.; Sitges, M. (European Heart Journal, 2021)
Background: Myocardial deformation integrated with cardiac dimensions provides a comprehensive assessment of the ventricular remodelling patterns induced by cumulative effects of intensive exercise. Feature tracking(FT) can measure myocardial deformation from cardiac magnetic resonance(CMR) cine sequences; however, its accuracy is still scarcely validated.